Due semantiche del 'vedere' ne I giorni e gli anni di Uwe Johnson (Altre Modernità, 2015)
The present study addresses two questions. First, how do extra-textual elements become, by means of fiction, aesthetic structures? Second, which function can be traced back to the 'window' as a space of enunciation? Through an analysis of a chapter of «Anniversaries» of Uwe Johnson, we aim to reveal how the description of an event gives rise to two different semantics of 'viewing'. Whereas the window figures on the one hand as a mere frame which comes between the outside and inside – i.e., between the subject and the object that is meant to be represented – on the other hand the window is elevated to the function of an authentic mode of knowing. This analysis shows that the two semantics of 'viewing' create a space of enunciation. In the first case, the act of 'viewing' coincides with the principle of imitatio naturae, whereas in the second case, one witnesses images one after the other, which are defined by the act of 'viewing', as a prolongation of past events. The effect of this rhetorical device becomes evident in a shift of interest from the question of reference, to the question of mediation between 'configuration' and 'postfiguration'.